Respuesta :
For this case we have a function of the form:
y = A (b) ^ x
Where,
A: initial amount
b: growth rate
x: time (in months)
We have the following equation:
f (x) = 15 (3) ^ x
We observed that:
b = 3
Therefore, the number of bees triples each month.
Answer:
b = 3
the number of bees triples each month.
y = A (b) ^ x
Where,
A: initial amount
b: growth rate
x: time (in months)
We have the following equation:
f (x) = 15 (3) ^ x
We observed that:
b = 3
Therefore, the number of bees triples each month.
Answer:
b = 3
the number of bees triples each month.
Answer: C= the number tripled each month.
Step-by-step explanation: